2017
DOI: 10.1523/jneurosci.4601-15.2017
|View full text |Cite
|
Sign up to set email alerts
|

Linear Summation of Repulsive and Attractive Serial Dependencies: Orientation and Motion Dependencies Sum in Motion Perception

Abstract: Recent work from several groups has shown that perception of various visual attributes in human observers at a given moment is biased toward what was recently seen. This positive serial dependency is a kind of temporal averaging that exploits short-term correlations in visual scenes to reduce noise and stabilize perception. To date, this stabilizing "continuity field" has been demonstrated on stable visual attributes such as orientation and face identity, yet it would be counterproductive to apply it to dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
116
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(128 citation statements)
references
References 62 publications
12
116
0
Order By: Relevance
“…All subjects reported normal or corrected visual acuity, provided written informed consent, and were compensated monetarily. Sample size was chosen to be on par with recent serial dependence experiments which focus on group-level statistical inferences (Alais et al, 2017;Bliss et al, 2017;Fritsche et al, 2017), while also being large enough to detect the PEB, as per our prior work (Samaha et al, 2016). Data from this experiment were published previously as part of a multi-experiment study addressing different hypotheses .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All subjects reported normal or corrected visual acuity, provided written informed consent, and were compensated monetarily. Sample size was chosen to be on par with recent serial dependence experiments which focus on group-level statistical inferences (Alais et al, 2017;Bliss et al, 2017;Fritsche et al, 2017), while also being large enough to detect the PEB, as per our prior work (Samaha et al, 2016). Data from this experiment were published previously as part of a multi-experiment study addressing different hypotheses .…”
Section: Methodsmentioning
confidence: 99%
“…Serial dependence often manifests as a bias towards reporting that a current stimulus appears more similar to recently seen stimuli than it actually is. Serial dependence occurs for a range of stimulus features, including luminance (Fründ et al, 2014), orientation Fritsche et al, 2017), spatial location , direction of motion (Alais et al, 2017), numerosity (Fornaciai and Park, 2018), motion variance (Suárez-Pinilla et al, 2018), and higher-level features such as face identity (Liberman et al, 2014). Although suboptimal in a psychophysical task where stimuli are temporally uncorrelated, in many real-world scenarios stimuli are stable across various time scales and serial dependence may be an adaptive bias that promotes temporal continuity (Kiyonaga et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond orientation Fritsche et al, 2017;Liberman, Zhang, & Whitney, 2016;Manassi et al, 2017) and other basic features (motion: Alais, Leung, & Van der Burg, 2017;position: Manassi et al, 2018), serial dependence occurs at higher levels of perception as well. We have recently demonstrated that the continuity field is objectselective by showing that the perception of face identity is systematically biased towards identities seen up to several seconds prior, even across changes in viewpoint (Liberman et al, 2014; see also Taubert, Alais, & Burr, 2016;Taubert, Van der Burg, & Alais, 2016;Xia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Anstis, 1982) to gender of human voices (Schweinberger et al, 2008) and even vocal affect 13 (Bestelmeyer et al, 2010). While the classical paradigm usually involves long periods of 14 adaptation, sizeable negative aftereffects can arise after very brief presentations in vision as 15 in audition (Aagten-Murphy and Burr, 2016; Alais et al, 2017Alais et al, , 2015. 16…”
Section: And Tone Intensity (Reinhardt-rutland and 12mentioning
confidence: 99%